Identifying and contextualising the motivations for BIM implementation in construction projects: An empirical study in China. Issue 4 (May 2017) - Cao, Dongping; Li, Heng; Wang, Guangbin; Huang, Ting
Abstract: Grounded in institutional theory and the innovation diffusion literature, this paper identifies the motivations of designers and general contractors to implement BIM in construction projects, and investigates how different motivations are impacted by organisational BIM capability and other contextual factors. Results of factor analysis with survey data collected from China provide support for the theoretically developed motivation model which classifies BIM implementation motivations into four categories: image motives, reactive motives, project-based economic motives, cross-project economic motives . Hierarchical regression results suggest that although project participants will have stronger economic motivations to improve project performances as their BIM capability matures, this increase in economic motivations does not necessarily require a parallel decrease of desires to improve social image. Regression results also suggest that BIM implementation motivations relate to organisational ownership type and project characteristics. The findings contribute to a broadened understanding of the multi-dimensionality and dynamics of construction organisations' innovation implementation motivations. Highlights: Motivations for BIM implementation in construction projects are classified into four categories. Social and economic motives are not mutually exclusive as conventional wisdom might indicate. BIM capability increases project-based economic motives but is not related to other motives. BIM implementation motives relate to organisational ownership type and project characteristics.